Stable current sheath dynamics caused by preionization source in a small plasma focus device using He as an operating gas. Issue 3 (3rd April 2019) - Khan, H.U.; Hussain, S. S.; Ikram, M.; Ilyas, M. Zafar; khan Niazai, M. Zubair; Shafiq, M.
ABSTRACT: Pinching of the current sheath in the plasma focus (PF) device is an important phase to transfer the stored energy to the high density short lived plasma for the production of a group of useful radiations. The current sheath formation during the initial breakdown of the gas is a critical process in the PF operation. In this regard, the understanding of the current sheath dynamics is of prime importance. In this paper, we present the effects of alpha particle induced preionizaion by U 238 in 3.3 kJ He operated PF device on the dynamics of current sheath, focus amplitude and axial rundown velocity by employing Rogowski coil and High voltage probe as main diagnostic tools. The formation of parabolic axisymmetric sheath is confirmed by Rogowski coil and high voltage probe signals which also reveals the variation in focusing time as well as amplitude during collapse phase by using the preionization source. Time resolved X-ray diagnostics are also carried out using PIN diodes covered with Al and Mg filters of 12.5 and 25 µm which provide an important information about an early onset of X-ray generation. Time integrated X-ray imaging is also carried out to estimate X-ray production zone in the PF device indicating enlarged and symmetric images with preionization.